Airport noise mapping - a case study at İstanbul Sabiha Gökçen International Airport - Keskin, Oya; Yılmaz, Sevtap (My University, 2015)
One of the problems brought about by the developing technology is the noise problem. This problem which comes out by variety of sources and threates human health, targets developed and developing countries on taking measure for noise. At this point, one of the largest sources of the formation of environmental noise is airports for certain. Noise mapping can be defined as the disturbance of population who lives in a specified territory and the assesment of environmental noise that population is exposed to. Considering the environment which is developing and changing, studies on noise mapping should be renewed for a period of five years. The aim of this study is preventing random heights of housing and by doing so defining where the boundries of settlement territory according to noise and considering master plans that are suppose to be used by urban planners. Moreover, encouring sound isolation for the new housing that are going to be built within the noise territories that can be detected from the noise mapping of this areas. Mappings which are obtained by SoundPlan computer simulation program, show zones that are effected by aircraft noise from 50 dBA to 85 dBA. Additionally, percent of buildings which are located in the danger zone, specifing for day, evening and night by regulations, are obtained and the amount of population affecting by the noise is figured.
Airport noise mapping - a case study at İstanbul Sabiha Gökçen International Airport
Keywords: Environmental noise; aircraft noise; noise mapping; Sabiha Gökçen International Airport